The Influence of Budget Participation, Organizational Commitment, and Total Quality Management (TQM) on Managerial Performance (Empirical Study at Bank Mandiri and Bank Central Asia in Jambi City) - Amelia, Putri; Yuliusman, Yuliusman; Jumaili, Salman (Jurnal Cakrawala Akuntansi, 2023)
This study aims to examine the effect of variable Budget Participation, Organizational Commitment and Total Quality Management (TQM) on Managerial Performance at Bank Mandiri and Bank Central Asia in Jambi City. This study uses a saturated sampling technique. Research data collection was carried out by distributing questionnaires to 70 respondents, and questionnaires that could be used were only 62. Data processing using SPSS 22.0 software. Before testing the hypothesis, an instrument quality test and a classic assumption test are performed. The results of testing the quality of the instrument consisting of validity and reliability tests show that all question items are valid and reliable. The results of the classic assumption test which consists of data normality test, multicollinearity test, and heteroscedasticity test show that all data meet the requirements. Hypothesis testing results indicate that simultaneous budgetary participation, organizational commitment and total quality management (tqm) affect managerial performance. Partially, only organizational commitment and total quality management (tqm) variables affect managerial performance, while budgetary participation variables do not affect managerial performance.